Tajikistan spatial: A national development and food security atlas - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
TAJIKISTAN SPATIAL provides policy makers and the research community with the information needed to support evidence-based policies and strategies that target increased productivity, reduced poverty, and improved food and nutrition security. Tajikistan Spatial is a collaborative project involving the International Food Policy Research Institute (IFPRI) and the University of Central Asia (UCA), Local Development Committee under the President of the Republic of Tajikistan (LDC), supported by the CGIAR Research Programs on Policies, Institutions, and Markets (PIM) and Agriculture for Nutrition and Health (A4NH), the Ministry of Finance of the Russian Federation, and the International Fund for Agricultural Development (IFAD).